Comparative analysis of expression profiles of metacaspase (MC) genes between two apple (Malus domestica) cultivars with distinct ripening behavior. Issue 12 (12th September 2022) - Lv, Jingyi; Sun, Mingyu; Zhang, Yingzhi; Chen, Jingxin; Ge, Yonghong; Li, Jianrong
Abstract: The purpose of this research was to determine expression profiles of metacaspase ( MC ) genes during ripening and senescence of two apple cultivars with distinct ripening behavior. "Golden Delicious" and "Fuji" harvested at commercial maturity were used as materials. Our data revealed that flesh firmness, respiration rate, ethylene production, metacaspase (MC) activity, superoxide anion (O2 − ) production rate, relative electrical conductivity (REC), hydrogen peroxide (H2 O2 ), and malondialdehyde (MDA) contents in "Golden Delicious" were higher than in "Fuji" during ripening. At 35 days, no DNA ladder was observed in both cultivars, and tonoplast disintegration was only observed in "Golden Delicious" by transmission electron microscope (TEM), indicating that programmed cell death (PCD) was initiated earlier in "Golden Delicious" than in "Fuji." A total of 18 MC genes were detected to be expressed in both cultivars. For those genes expressed only in "Golden Delicious, " MdMC06, MdMC10, MdMC12, and MdMC21 might play a role in the early stage of ripening, whereas MdMC19 might be associated with the late stage of ripening. MdMC15 was expressed only in "Fuji." The remaining MC genes were differentially expressed in both cultivars during ripening. These results would provide useful information to further underlie the relationships among MC genes, PCD and storability of different apple cultivars. Practical applications: Apple is one of the most popular fruits in the world. Different apple cultivars vary in their ripening behavior and storability, but the molecular mechanism has not yet been fully elucidated. "Golden Delicious" and "Fuji" are two important apple cultivars worldwide. Our data indicated that PCD was initiated earlier in "Golden delicious" than in "Fuji" during postharvest ripening and senescence. MdMCs showed variable expression patterns in both cultivars during ripening. MdMC15 and MdMC19 might be closely associated with the early stage of PCD. These results would provide useful information to further decode the molecular mechanisms responsible for different storage storability of apple cultivars. Abstract : MdMCs had varying expression patterns in "Golden delicious" and "Fuji" during ripening. PCD was initiated earlier in "Golden delicious" than in "Fuji" based on TEM and DNA ladder assay.